Analysis of the Implementation of Quipper Learning in Facilitating the Understanding of Derivatives of Trigonometric Functions in High School - Hamdanah; Iyan Rosita Dewi Nur (Universitas Suryakancana, 2026)
The use of Quipper media in teaching trigonometric function derivatives strengthens learning outcomes compared to conventional methods. The analysis shows that Quipper produces higher posttest scores and N-Gain values, reflecting better conceptual mastery and optimal learning engagement. The findings confirm that Quipper is a digital learning medium that is more effective, especially for abstract and complex mathematical material. Future studies can utilize Quipper for different mathematical concepts or integrate it with technology-based learning models to further improve learning performance and motivation.